2005
DOI: 10.1038/sj.mp.4001682
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptor contribution to the action of PCP, LSD and ketamine psychotomimetics

Abstract: Although phencyclidine and ketamine are used to model a hypoglutamate theory of schizophrenia, their selectivity for NMDA receptors has been questioned. To determine the affinities of phencyclidine, ketamine, dizocilpine and LSD for the functional high-affinity state of the dopamine D2 receptor, D2 High , their dissociation constants (K i ) were obtained on [ 3 H]domperidone binding to human cloned dopamine D2 receptors. Phencyclidine had a high affinity for D2 High with a K i of 2.7 nM, in contrast to its low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(106 citation statements)
references
References 37 publications
3
93
1
1
Order By: Relevance
“…Importantly, this is consistent with neurotransmitters levels observed during REM sleep (Trulson and Jacobs, 1979;Park et al, 1999;Lena et al, 2005), and during the waking period of DAT-KO mice immediately after exposure to novelty (Gainetdinov et al, 1999(Gainetdinov et al, , 2001). This also predicts that psychosis may be generated by pharmacological agents that activate the D 2 dopamine receptor while altering specific aspects of glutamatergic or serotonergic transmission (Kapur and Seeman, 2002;Seeman et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this is consistent with neurotransmitters levels observed during REM sleep (Trulson and Jacobs, 1979;Park et al, 1999;Lena et al, 2005), and during the waking period of DAT-KO mice immediately after exposure to novelty (Gainetdinov et al, 1999(Gainetdinov et al, , 2001). This also predicts that psychosis may be generated by pharmacological agents that activate the D 2 dopamine receptor while altering specific aspects of glutamatergic or serotonergic transmission (Kapur and Seeman, 2002;Seeman et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, drugs that increase endogenous dopamine release (e.g., amphetamines) were found to induce psychosis in healthy individuals and exacerbate psychotic symptoms in schizophrenic patients (Snyder, 1972). Recent evidence also suggests that other pharmacological agents that induce psychosis in healthy individuals (e.g., PCP) demonstrate significant potency for the D 2 dopamine receptor (Kapur and Seeman, 2002;Seeman et al, 2005).…”
mentioning
confidence: 99%
“…Another study used 26 of the BXD RI strains and found no evidence for a genetic correlation between the locomotor stimulant responses to phencyclidine and methamphetamine (Alexander et al, 1996). Therefore, although both drugs can produce psychotic states in humans, and they share the involvement of dopamine in their behavioral effects (Del Arco et al, 2007;Seeman et al, 2005;Zhang et al, 2001), the genetic mechanisms that determine sensitivity to these drugs may be disparate. Janowsky et al (2001) made use of a large database of BXD RI strain means for multiple drug-related traits to identify genetic correlations with DAT density.…”
Section: Inbred Strain Studiesmentioning
confidence: 99%
“…Besides its well-established NMDAR antagonism, PCP also acts as a D2 receptor (D2R)-like agonist. [46][47][48] We performed a battery of molecular and behavioral tests that revealed a preserved D2R neurotransmission in Ddo − / − mice, thus corroborating a glutamatergic origin for the different responsivity to PCP observed in Ddo − / − mice (see Supplementary Information and Supplementary Figure S2). fMRI response induced by PCP in Ddo − / − mice Because D-Asp can modulate NMDAR-related functions, [18][19][20][21]38 we used Ddo − / − mice to assess whether genetically driven D-Asp elevation can modulate the aberrant neurofunctional cascade underlying the psychotomimetic effect of PCP.…”
Section: Resultsmentioning
confidence: 99%